Overworked or underemployed? Actual and preferred household employment patterns in the context of the economic crisis - Nadia Steiber; Barbara Haas (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
This article revisits work hour mismatches at the couple level. Most of what has been published on actual and preferred employment arrangements of couples in Europe is based on international survey data from the late 1990s. The aim is to present new data on couples' actual and preferred employment arrangements using data from Round 5 of the European Social Survey (2010-2012). The article discusses trends in the degree to which couples' employment arrangements are in line with preferences and how work hour mismatches may be related to the current economic crisis.
Keywords: 300; couple employment; European Social Survey; labour supply; preferences; economic crisis